Swimming-induced changes in pulmonary function: special observations for clinical testing - Päivinen, M.; Keskinen, K.; Tikkanen, H. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background A special improvement in pulmonary function is found in swimmers. In clinical testing the airway reactivity is observed at certain exercise intensity and target ventilation. However, in highly trained swimmers exercising in water the reactions may not function the same way. The aim was to study the combined effects of the water environment and swimming on pulmonary function and the associations with perceived symptoms.